Molas Baju Wara: Hybridity in Manggarai Rap Music - Ans. Prawati Yuliantari (Celt: A Journal of Culture, English Language Teaching & Literature, 2016)
Rap music which has been popular since 2007 in Manggarai region, East Nusa Tenggara, Indonesia, gave rise to rap hybrid phenomenon. The mixture between American rap music formats and local elements of Manggarai attracted the attention of young people in the region. One of the local songs that feature hybridity in rap Manggarai is "Molas Baju Wara" created by Lipooz, one of the pioneers of rap in Ruteng, the capital city of Manggarai district. To discuss this phenomenon, the concept of hybridity in cultural territory proposed by James Lull is adopted. This concept is used particularly to analyze the forms of hybridity reflected in " Molas Baju Wara" and the ways they are used in showing the social and cultural conditions of Manggarai. "Molas Baju Wara" was selected as the object of study because the song is clearly showing the characteristics of hybridity in music. The study shows that hybridity could be perceived in Manggarai rap music specifically in the use of local musical instruments like drums, cajon, and tambourine as a substitute for percussive sounds of drums, boombox, or turn-table which are commonly used by rap musicians in their home country, the U.S.A. In addition, there are elements of local sound such as the sound of rain that represents Ruteng as the rain city. Hybridity characteristics can also be found in the use of Manggarai vernacular in the whole lyrics as well as the narration of local themes and certain sites that represent Ruteng.